KNOWLEDGE AND PRACTICE OF MATERNAL HEALTH CARE IN INDONESIA - Teguh Sugiyarto (Research Centre for Population, Indonesian Institute of Sciences, 2007)
This article is aimed to discuss the utilisation of maternal health facilities by pregnant women during the pregnancy, delivery and postnatal care in Indonesia. The description about women's knowledge to understand the danger signs of pregnancy complication is also presented. Furthermore, to some extent, the effect of the women's knowledge about the danger signs of pregnancy complication to influence the utilization of maternal health care can be analysed by using Indonesia Demographic and Health Survey (IDHS) 2002-2003. It is very important to understand the factors that determine the utilization health facility since the main causes of maternal dead are preventable. IDHS 2002-2003 show that utilization of maternal health care is relatively low, especially for delivery care and postnatal care. Moreover the women's lmowledge about danger signs of pregnancy complication is also low. In addition The Mann-Whitney test shows that women who utilized maternal care services and who did not utilized maternal care services have different score of knowledge. It can be said that women's knowledge is more likely influence the utilization of maternal health care.Key words: Pregnant women, Utilization of health facilities, Health's lmowledge